2011
DOI: 10.1159/000328729
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Penetration of a Skin Sensitizer and Its Delivery Vehicles Simultaneously with Confocal Raman Spectroscopy

Abstract: Among the factors determining the propensity of a chemical to induce skin allergy are the penetration into skin and the kinetics of ingress. Confocal Raman spectroscopy can provide such information as it enables direct, spatially resolved measurement of the skin and of any chemical uptake. Several chemicals can be monitored at once, and the method is non-destructive (light in, light out) so that the skin can be kept intact for repeated and continuous measurement. Raman spectroscopy was used to follow the penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 90 publications
0
27
0
Order By: Relevance
“…They were custom built and inspired by the devices used by Ashtikar et al [4] and Bonnist et al [13]. The choice of device depended on the analysis time (closed device for longer duration) and whether the objective was or could be corrected for use with a coverslip (table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were custom built and inspired by the devices used by Ashtikar et al [4] and Bonnist et al [13]. The choice of device depended on the analysis time (closed device for longer duration) and whether the objective was or could be corrected for use with a coverslip (table 2).…”
Section: Methodsmentioning
confidence: 99%
“…The increasing use of CRM to establish skin penetration profiles has led to an increasing variety of microscope configurations and sample preparation methods used therein (table 1) [3,4,13,14,15,16,17,18,19,20,21,22,23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…this continuum PDe approach is of particular importance for describing ingredient transport across compartments with high spatial heterogeneity, such as the stratum corneum. Parameterization of the required macro diffusion rates can be achieved by fitting to clinical data encompassing tape stripping, TEWL, or Raman confocal microscopy measurements (Herkenne et al, 2008;Bonnist et al, 2011). However, through consideration of the structure and hydrophobicity of lipid bilayers and corneocytes, significant effort has been made to determine the required diffusion and partition coefficients using only physicochemical range of chemical properties relevant to consumer products, an understanding of the relative rates of the above skin toxicokinetic events and processes is required.…”
Section: Toxicokinetics Of Skin Allergymentioning
confidence: 99%
“…A number of approaches, such as tape stripping and Raman spectroscopy, can be used to determine ingredient concentration in the upper layers of the stratum corneum and the epidermis, but deeper layers are only accessible via disruptive procedures such as micro-dialysis and punch biopsies (Holmgaard et al, 2010;Bonnist et al, 2011;Wang and Maibach, 2011). evaluation of such models over a wide range of ingredient chemistries and formulations is a challenging prospect.…”
Section: Toxicokinetics Of Skin Allergymentioning
confidence: 99%
“…In the past, it had been assumed that topically applied substances penetrate exclusively via the intercellular route, i.e., inside the lipid layers around the corneocytes [27,28,29]. Recently it was demonstrated that the hair follicles represent an efficient penetration pathway for topically applied substances [30,31,32].…”
Section: Follicular Penetrationmentioning
confidence: 99%